Knowledge, Attitude and Practice on Preventive Dentistry among Senior Dental Students in Yemen - Mohammed Ali, Mohammed Al-Wesabi; Zaleha, Md Isa (Universiti Kebangsaan Malaysia, 2015)
Introduction: There is a strong and increased worldwide interest on the aspects of prevention of oral disease and oral health promotion in dental education. However, some studies imply that dental students are not knowledgeable enough in this issue. This study aimed to evaluate the knowledge of, attitude towards and practice on preventive dentistry among senior dental students in Yemen. Methods: Self-administered questionnaires were distributed among senior dental students in six dental schools in Yemen. The questionnaire obtained personal information, and questions about knowledge on preventive dental care, attitudes towards and practice on preventive dentistry. Results: Among 346 students who filled the questionnaire, a total of 91.6% has good knowledge about fissure sealant effectiveness, only 34.7% knows about the importance of fluoride toothpaste compared to brushing technique in preventing caries, with significant gender difference (p=0.005). Odds of good knowledge among non-Qat chewers was 1.9 (95%CI: 1.26-4.42). Multivariable regression analysis indicated that female gender was associated with higher positive attitudes (OR: 2.03, 95%CI:1.21-3.36,p=0.007). Attitudes were significantly associated with Qat chewing (OR = 1.95, 95%CI: 1.04-3.66, p=0.03), type of university (OR = 0.59, 95%CI: 0.36-0.94, p=0.02), and mothers' level of education (OR = 1.91, 95%CI: 1.05-3.47, p=0.03). There was a high percentage of competency in practicing preventive measures among students (80.9%). Conclusions: Dental education should emphasize the overall aspects of preventive dentistry with early exposure of preventive dental training in order to improve students' knowledge and attitudes and consequently practice on preventive care.